Policy and regulatory perspectives of waste battery management and recycling: A review and future research agendas - Md Tasbirul Islam; Amjad Ali; Sikandar Abdul Qadir; Muhammad Shahid (Waste Management Bulletin)
Waste batteries represent a critical waste stream due to their valuable materials and potential environmental hazards. Existing studies predominantly focus on recycling methods, technologies, and material recovery, often relegating policy and regulatory considerations to secondary or partial analyses. Notably, no comprehensive review exclusively addressing the policy and regulatory dimensions of waste battery management has been conducted. To fill this gap, this study systematically reviewed 135 original research articles using a systematic literature review (SLR) and content analysis, examining ten key aspects: (1) scope and definition, (2) collection systems, (3) recycling and processing standards, (4) producer responsibility, (5) public awareness and education, (6) regulatory framework, (7) incentives for recycling, (8) research and development, (9) data collection and reporting, and (10) partnership and stakeholder engagement. The findings highlight core policy elements essential for effective waste battery management, including multi-stakeholder collaboration, data-driven decision-making models, eco-friendly technology R&D, government oversight of informal recycling, lifecycle thinking, consumer participation through education campaigns, adoption of global best practices, and Extended Producer Responsibility (EPR) implementation. Additionally, the study proposes actionable policy statements tailored for countries lacking established waste battery policies. This research provides a foundational framework for policymakers and valuable insights for researchers in waste management, environmental policy, and public administration.